Bioaccumulation of Some Trace elements in muscles of two species of fishes inEuphrates River near the center of Suq Al-Shouyukh city- south Iraq - T. Farhood, Afaq (University of Thi-Qar Journal of Science)
The present study involved the estimation of the concentration of four trace elements (cadmium ,copper, lead and zinic) in muscles of two species of fishes Barbus luteus and Liza aba collected from the Euphrates river near Suq-Al-Shouyokh city center south of Iraq, during the period winter and summer 2014 , as an indicator for Bioaccumulation of some trace element into tropic level in the aquatic system :water – sediment – fishes , to statement bioaccumulation and biosedimentation of this elements. Also sediment texture and total organic carbon (TOC%) were measured. Analysis employing a flam Atomic Absorption Spectrophotometers .The trace elements were studjed in dissolved and particulate phase of water , in sediment and muscle of this fish ,and recorded bioaccumulation factor (BAF) and biosedimentation factor (BSF) to element above :( 2100-1750 ); (1454 1090);(2172-1830);(1738-1571) respectively concentration as much once in the water, and (0.5-0.42);(0.480.35);(0.58-0.84);(0.21-0.19) respectively concentration as much once in the sediment . The statistical analysis didn’t show a significant correlation between most element in sediment and total organic carbon as well as sediment texture .In conclusion the present study , trace elements concentration in particulate phase was higher than their concentrations in the dissolved phase , sediment and muscles of fish , The order of trace element as follows: particulate phase < sediment < fishes muscles (Barbus luteus and Liza aba )<dissolve phase and also the trace elements in the follow order : Zn < Pb < Cu < Cd .And muscle of Barbus luteus able to accumulate higher from muscle Liza aba and that accumulate depend to study specie ,pattern of nutrition . Values of(BAF) were higher than those for(BSF)in muscles of fish species. And the result showed that trace element concentration in muscles of two were in the international acceptable limits ,so it can be safety having related to this type of pollutants now days . Considered good indicator of accumulation for trace element in water.